Recognising license plate from image data using deep learning - Golder, Rupam; Rahman, Sadman; Shams, MD. Isteak; Hasan, Jawad; Bakhtiar, Fahim Muhammad (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.